Detection of Neoehrlichia mikurensis DNA in blood donors in southeastern Sweden. Issue 10 (3rd October 2022) - Labbé Sandelin, Lisa; Olofsson, Jenny; Tolf, Conny; Rohlén, Louise; Brudin, Lars; Tjernberg, Ivar; Lindgren, Per-Eric; Olsen, Björn; Waldenström, Jonas
Abstract: Background: The tick-borne bacterium Neoehrlichia mikurensis can cause persistent asymptomatic bloodstream infections, but transfusion-mediated transmission has not been reported. This study aimed to investigate the prevalence of N. mikurensis in blood donors, and recipients of blood components from N. mikurensis -positive donors were traced. Methods: In 2019 and 2021, 1007 blood donors were recruited. Participants completed a questionnaire and additional blood samples were collected during blood donation. Detection of N. mikurensis was performed by PCR followed by sequencing. Positive donors were interviewed and retested. Look-back was performed on positive donations and on all subsequent donations. Results: N. mikurensis was detected in 7/1006 (0.7%) donors. A total of 380/1005 (38%) donors reported at least one noticed tick bite during the current season. The questionnaire could not detect any differences between negative and positive N. mikurensis -donors. Two of the positive donors were still positive on days 318 and 131 after the index donation, respectively. One donor with persistent N. mikurensis in blood experienced slight fatigue. All other had no symptoms attributable to neoehrlichiosis. Look-back included ten donations and 20 blood components. Eight components were discarded, and 12 recipients of N. mikurensis -positive donations were identified. PCR was negative in seven recipients. Five recipients had died, but their medical records gave no evidence for neoehrlichiosis. Conclusions: Although N. mikurensis was found in 0.7% of blood donors, transfusion-mediated infection was not detected, despite several recipients being at high risk for severe neoehrlichiosis. The results warrant further studies as well as raised clinical awareness.